Different intestinal permeability patterns in relatives and spouses of patients with Crohn's disease: an inherited defect in mucosal defence?. Issue 1 (1st January 1999) - Söderholm, J D; Olaison, G; Lindberg, E; Hannestad, U; Vindels, A; Tysk, C; Järnerot, G; Sjödahl, R
Abstract : Background: A familial defect in intestinal barrier function has been found in Crohn's disease. Aim: To investigate possible genetic and environmental influences on this barrier defect by studying intestinal permeability in both relatives and spouses of patients with Crohn's disease. Subjects: The study included 39 patients with Crohn's disease, 34 healthy first degree relatives, and 22 spouses. Twenty nine healthy volunteers served as controls. Methods: Intestinal permeability was assessed as the lactulose:mannitol ratio in five hour urinary excretion after oral load, both before (baseline) and after ingestion of acetylsalicylic acid. The permeability response represents the difference between the two tests. A ratio above the 95th percentile for controls was classified as abnormal. Results: Baseline permeability was higher in patients and spouses than in controls. An abnormal baseline permeability was seen in 36% of the patients, 23% of the spouses, 18% of the relatives, and 3% of the controls. After ingestion of acetylsalicylic acid, permeability increased significantly in all groups. Relatives were similar to patients with regard to permeability after exposure to acetylsalicylic acid, whereas spouses were similar to controls. The proportions with an abnormal permeability response to acetylsalicylic acid were 32% in patients, 14% in spouses, 41% in relatives, and 3% in controls. Conclusion: The findings suggest that baseline permeability is determined by environmental factors, whereas permeability provoked by acetylsalicylic acid is a function of the genetically determined state of the mucosal barrier, and support the notion that environmental and hereditary factors interact in the pathogenesis of Crohn's disease.